The Impact Of COVID-19 Lockdown on Parents Handling Children with Disability in Chennai, India - Palaniappan, Pragadeesh; Patel, Rashmi Gour; B, Krishna Prasanth Baalann; Umadevi Ramachandran; BN Surya; Supraja Nagarathinam (National Journal of Community Medicine, 2023)
Introduction: Millions around the globe were directly or indirectly affected by COVID-19 pandemic. The COVID-19 epidemic has harmed the lives of children with special needs in many ways, whether directly or indirectly. Few studies have evaluated the Impact of covid-19 lockdown among children with disability. However, the Impact of COVID on parents dealing with special children was scarcely studied in detail. Investigating parental stress, worries, and morbidity during the lockdown is particularly important for assisting these parents during further outbreaks. The aim is to assess the Impact of covid-19 lockdown among parents handling disabled children, parenting stress, their concerns, and morbidity during the COVID-19 lockdown. Materials And Method: The study was done among the parents of disabled children attending special schools in Chennai, using a cross-sectional study design. Parents with any recent trauma, mental disorders, or major diseases and undergoing treatment for themselves were excluded. After obtaining ethics approval, a semi-structured questionnaire was used to assess the Impact of the covid-19 lockdown. Collected data were analyzed using SPSS v.21. Results: The study includes 305 parents, predominantly mothers (58%) and the mean age was 38.9+8.2 years. We observed that the COVID-19 lockdown impacted 149 parents (48.9%). The significant predictors for the Impact of COVID-19 lockdown were being a single parent [AOR-2.91(95%CI- 1.05-8.08)] and having a part-time job [AOR-0.36(95%CI- 0.14-0.93)]. Conclusion: The COVID-19 outbreak and lockdown significantly impacted the parents of disabled children. It is high time we give importance to these parents of children with special needs during this pandemic to help them during similar occasions in the future.